412 Knowledge and Practices for the Prevention of the Diabetic Foot in North Wales. (19th August 2022) - Morris, R; O'Malley, J; Gilliland, E; Shaikh, F
Abstract: Aim: Diabetes mellitus can result in a wide range of foot complications such as ulceration, infection, and amputation. The National Institute for Health and Care Excellence (NICE) recommend that all diabetic patients should receive verbal and written information relating to their foot care. Here we assess our compliance with the national guidelines and the levels of patient knowledge amongst the diabetic population in the North West of Wales. Method: A questionnaire was provided to all adult diabetic patients attending the outpatient podiatry service over the course of three weeks at Ysbyty Gwynedd, North Wales. The survey included compliance and knowledge-based questions regarding foot care. Results: A total of 65 patients were recruited and completed questionnaires. The majority of the patients were males (male:female ratio 2:1) and over 70 years and had type II diabetes. 98% of patients admitted to receiving verbal diabetic advice while only 57% received written information. Compliance with daily foot checks was 82%. Regarding patient knowledge, over 90% of patients selected the correct answer to 11 out of the 15 knowledge-based questions. Despite 95% recognising that poor footwear can contribute to diabetic foot complications, only 86% recognised that walking barefoot carries similar risks. Conclusions: Diabetic foot knowledge is high within our studied population. Use of patient information leaflets can be further improved to help educate patients in avoiding barefoot walking and to prevent diabetic foot complications and limb loss.